Motion Sickness: Holding the Acupressure Point of Village-Owned Business Entities on the Wheel of “Good Corporate Governance” - Dewi, Amelia Sri Kusuma; prasetyo, Ngesti Dwi; Rifan, Mohamad; Habsari, Hanugrah Titi (Faculty of Law, Universitas Brawijaya, 2024)
The transcription of Good Corporate Governance (GCG) scenarios in various state regulations basically attempts to build plots to move various economic resources from an area with low productivity to an area with higher productivity with greater results. However, this condition is different when the Indonesian Government wants Village-Owned Enterprises (BUMDes) which normatively and culturally are not designed for entrepreneurship like BUMD/BUMN. The consequence of this desire is that in its implementation BUMDes tends to be neglected and not bound by the principles of Good Corporate Governance (GCG). Through juridical-normative research methods and 3 (three) legal approaches, this research focuses on